2005
DOI: 10.1152/ajplung.00428.2004
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility of purinergic receptor-deficient mice to lung infection withPseudomonasaeruginosa

Abstract: Rice. Increased susceptibility of purinergic receptor-deficient mice to lung infection with Pseudomonas aeruginosa. Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Our data show that purinergic agonist ATP␥S applied intravenously produces a beneficial effect in an LPS-induced model of ALI, reducing accumulation of inflammatory cells and total protein in lungs. As a recent study showed, P2Y 1 /P2Y 2 Ϫ/Ϫ mice infected with P. aeruginosa accumulated more water and total protein in lungs than did wild-type mice, suggesting impaired epithelial/ endothelial barrier in purinergic receptor-deficient mice (11). Our in vitro data shows that ATP␥S promotes the restoration of endothelial barrier after LPS-induced injury.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our data show that purinergic agonist ATP␥S applied intravenously produces a beneficial effect in an LPS-induced model of ALI, reducing accumulation of inflammatory cells and total protein in lungs. As a recent study showed, P2Y 1 /P2Y 2 Ϫ/Ϫ mice infected with P. aeruginosa accumulated more water and total protein in lungs than did wild-type mice, suggesting impaired epithelial/ endothelial barrier in purinergic receptor-deficient mice (11). Our in vitro data shows that ATP␥S promotes the restoration of endothelial barrier after LPS-induced injury.…”
Section: Discussionsupporting
confidence: 67%
“…Extracellular ATP is critical for survival of pulmonary endothelial and epithelial cells in high oxygen and ozone concentrations (3). A recent study on transgenic mice showed that P2Y 1 and P2Y 2 receptors exert a protective role against infection of the lungs by Pseudomonas aeruginosa by decreasing protein leak (11). ATP, either released from cells or exogenously applied, protects against reperfusion-induced failure of the coronary endothelial barrier (13).…”
mentioning
confidence: 99%
“…Interestingly, while most of the purinergic receptors in KO mice display no aberrant phenotype under homeostatic conditions (48), the phenotypic consequences of their deficiencies become evident when KO mice are subjected to ischemia (49), infection (50), or bleeding (51,52), suggesting the pivotal roles of purinergic receptor in a variety of pathophysiological conditions. UDP-glucose (UDP-Glc) has been proposed as a ligand for the P2Y 14 receptor (53).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ATP receptor (P2Y 1 -R and P2Y 2 -R)-deficient mice exhibit impaired inflammatory responses and difficulty eradicating Pseudomonas from the lung [21]. Similarly, mouse strains with modest increases in lung adenosine have enhanced interleukin (IL)-4-mediated inflammatory responses [22], and higher lung AFFILIATIONS *Pediatric Pulmonology, adenosine levels lead to airway inflammation and pulmonary fibrosis [23,24].…”
mentioning
confidence: 99%